Unmasking governance failures: The impact of COVID-19 on small-scale fishing communities in South Africa. (November 2021) - Sowman, M.; Sunde, J.; Pereira, T.; Snow, B.; Mbatha, P.; James, A.
Abstract: The COVID-19 pandemic has highlighted the pre-existing vulnerability of the small-scale fisheries sector in South Africa and exposed the structural inequalities and ongoing injustices facing this sector. The failures within the fisheries governance and management system linked to the slow pace of implementing the Small-scale Fisheries Policy of 2012, have further exacerbated their vulnerability. This paper explores the immediate impacts of the COVID-19 pandemic on the small-scale fisheries sector and exposes how governance failures within the fisheries sector have increased their vulnerability. Restrictions on fishing activities and mobility, closure of conservation areas, unfair fines and arrests, loss of markets and barriers to sale of fish products as well as lack of access to water, have had significant impacts on small-scale fishers and coastal communities. The lack of social protection and the limited emergency relief provided by government further exacerbated their precarious position. Despite their vulnerability, fishers have demonstrated a measure of resilience, supporting those in need with food, lobbying government to amend restrictions and recognise their rights, and challenging efforts to fast-track development and exclude their voices. The crisis has highlighted an urgent need for broad, national level transformation to deal with the poverty and injustices facing poor coastal communities, as well as fisheries-specific policy reform.